Number theory games in the service of developing logical and algorithmic thinking - Főző Hajnalka; Kuchinka Katalin; Кучінка Каталін; Kucsinka Katalin (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. This research investigates the pedagogical efficacy of number theory games (focusing on divisibility, primality, and modular arithmetic) in enhancing computational skills. The aim is to demonstrate that by embedding core mathematical concepts within a gamified framework, we can actively foster students' logical inference, combinatorial skills, and conscious algorithmic thinking. This digital approach supports abstraction and the systematic development of error correction strategies. Number theory games can serve as effective tools in mathematics and computer science education, as they simultaneously enhance logical, combinatorial, and algorithmic thinking. This research aims to explore how divisibility, prime number, and modular arithmetic games can be used to develop students’ digital literacy and systems thinking. The playful learning environment supports independent problem-solving, the development of abstraction skills, and the awareness of error correction strategies. The methodological framework is based on the principles of discovery learning and gamification, which several studies have found effective in developing algorithmic thinking. Ihsan and Karjanto [1] emphasize that the playful teaching of combinatorial thinking promotes the understanding of algorithmization and logical consistency. According to Kovtaniuk et al. [2], digital simulations and educational games are particularly effective in enhancing algorithmic thinking, as they create interactive, feedback-based learning environments. Gundersen and Lampropoulos [3] highlight that the use of serious and digital games increases students’ motivation and promotes the integration of computational thinking into education.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: number theory games; mathematics education